Dilemma of mathematics - Azram, Mohammad (2014)
The pursuit of knowledge and the use of reason, based on sense and observation is a key ingredient for research. Mathematics is a creation of human mind concerned chiefly with ideas, processes and reasoning. In this paper, we will try to give a new comprehensive definition of mathematics to understand “what is mathematics”. We will discuss the controversial nature and position of mathematics and its scientific status. We will highlight the position of mathematics in different civilizations. We will highlight the mythical issues about Mathematics. We will also discuss the current state of mathematics i.e. mathematics in crises, especially pure mathematics and will put forward the remedial suggestions. We have gathered together some of these impressions; these are all tentative, nothing final about them, but these are here nonetheless.